Tinjauan Atas Kesiapan Kementerian Pekerjaan Umum Dan Perumahan Rakyat Terkait Keikutsertaan Indonesia Dalam Government Procurement Agreement (GPA) - Hestuleksono, Aryo (Veritas et Justitia, 2016)
AbstarctBasically ratification of the GPA for Indonesia is the opening of the Indonesian market (market access) to the entrepreneur/companies from other countries, which means allowing entrepreneur/foreign companies to participate in the process of procurement of goods and services (PBJ) government in Indonesia. Similarly, the reverse with Indonesian companies. The existence of market acess makes the relation between national with international law. This is a reason of  authors are interested to know further the relationship conformity with international law related to the readiness of the national Ministry of Public Works and Public Housing (PUPR) when Indonesia ratified the GPA views of the setting methods for selecting/ auction in the construction sector in national legislation. The method used is a normative juridical research and the purpose of research to give recommendation to the Ministry PUPR particularly regarding setting methods for selecting the procurement of construction services when Indonesia ratified the GPA. If viewed from the side PBJ arrangements in the Government in the field of construction, especially regarding the purpose, principles and method of election of, the results showed that Ministry PUPR not ready when Indonesia ratified the GPA, because there is a difference between setting purpose PBJ contained in Perpres No. 54/2010 and its amendments as well as Permen PU No 07/2010 and amendments that more give protection to national companies, while GPA has the open principle. In addition there are differences about the method of selecting good views of the types/forms (nomenclature) and its meaning. So that when Indonesia will ratify the GPA, the Government and the Ministry PUPR in particular need to make adjustments to the "purpose" of regulation PBJ as contained in the Perpres/Permen PU with "purpose" contained in the GPA. Similarly, adjustments to the forms (nomenclature) and the meaning of the audition method.